(untitled) (Journal of Health Sciences, 2014)
Introduction: Pharmacovigilance is an arm of patient care. No one wants to harm patients, but unfortunately any medicine will sometimes do just this. Underreporting of adverse drug reactions by healthcare professionals is a major problem in many countries. In order to determine whether our pharmacovigilance system could be improved, and identify reasons for under-reporting, a study to investigate the role of health care professionals in adverse drug reaction (ADR) reporting was performed.Methods: A pretested questionnaire comprising of 20 questions was designed for assessment of knowledge, perceptions, practice and barriers toward ADR reporting on a random sample of 1000 healthcare professionals in Bosnia and Herzegovina.Results: Of the 1000 respondents, 870 (87%) completed the questionnaire. The survey showed that 62.9% health care professionals would report ADR to the Agency for Medicinal Products and Medical Device of Bosnia and Herzegovina (ALMBIH). Most of surveyed respondents has a positive perception towards ADR reporting, and believes that this is part of their professional and legal obligation, and they also recognize the importance of reporting adverse drug reactions. Only small percent (15.4%) of surveyed health care professionals reported adverse drug reaction.Conclusions: The knowledge of ADRs and how to report them is inadequate among health care professionals. Perception toward ADR reporting was positive, but it is not reflected in the actual practice of ADRs, probably because of little experience and knowledge regarding pharmacovigilance. Interventions such as education and training, focusing on the aims of pharmacovigilance, completing the ADR form and clarifying the reporting criteria are strongly recommended.